The Relationship Between Generalized Joint Hypermobility and Adhesive Capsulitis of the Shoulder - Yeliz TERZİ,; Kenan AKGÜN,; İlknur AKTAŞ,; Deniz PALAMAR,; Günay CAN4, (Archives of Rheumatology, 2013)
Objectives: This study aims to investigate the possible relationship between generalized joint hypermobility (GJH) and adhesive capsulitis (AC) of the shoulder. Patients and methods: A total of 240 patients were enrolled in this study, including 120 patients diagnosed with AC in a study group and 120 patients diagnosed with primary subacromial impingement syndrome in the control group. We evaluated the pain severity, range of motion of the shoulder joint, functional status, disability, and hypermobility in both groups. The Beighton score was used to evaluate the GJH while the revised Brighton criteria were utilized for the patients with benign joint hypermobility syndrome (BJHS). Results: In the adhesive capsulitis group, GJH was significantly rare (p<0.05) with only one patient (0.08%) whereas BJHS was not found. In the control group, nine patients (7.5%) had GJH, and five (4.2%) had BJHS. Conclusion: Our study results suggest that GJH may be a protective or preventive factor in the development of AC. In clinical practice, we believe that in GJH patients we can be more optimistic regarding the concern of the conversion of shoulder pain to AC. If this has already taken place, then these patients may respond more positively to treatment in cases involving GJH.